A mutation in IFT43 causes non-syndromic recessive retinal degeneration. (18th September 2017) - Biswas, Pooja; Duncan, Jacque L; Ali, Muhammad; Matsui, Hiroko; Naeem, Muhammad Asif; Raghavendra, Pongali B; Frazer, Kelly A; Arts, Heleen H; Riazuddin, Sheikh; Akram, Javed; Hejtmancik, J Fielding; Riazuddin, S Amer; et al.
Abstract: The aim of this work is to identify the molecular cause of autosomal recessive early onset retinal degeneration in a consanguineous pedigree. Seventeen members of a four-generation Pakistani family were recruited and underwent a detailed ophthalmic examination. Exomes of four affected and two unaffected individuals were sequenced. Variants were filtered using exomeSuite to identify rare potentially pathogenic variants in genes expressed in the retina and/or brain and consistent with the pattern of inheritance. Effect of the variant observed in the gene Intraflagellar Transport Protein 43 ( IFT43 ) was studied by heterologous expression in mIMCD3 and MDCK cells. Expression and sub-cellular localization of IFT43 in the retina and transiently transfected cells was examined by RT-PCR, western blot analysis, and immunohistochemistry. Affected members were diagnosed with early onset non-syndromic progressive retinal degeneration and the presence of bone spicules distributed throughout the retina at younger ages while the older affected members showed severe central choroidal atrophy. Whole-exome sequencing analysis identified a novel homozygous c.100 G > A change in IFT43 segregating with retinal degeneration and not present in ethnicity-matched controls. Immunostaining showed IFT43 localized in the photoreceptors, and to the tip of the cilia in transfected mIMCD3 and MDCK cells. The cilia in mIMCD3 and MDCK cells expressing mutant IFT43 were found to be significantly shorter ( P  < 0.001) than cells expressing wild-type IFT43 . Our studies identified a novel homozygous mutation in the ciliary protein IFT43 as the underlying cause of recessive inherited retinal degeneration. This is the first report demonstrating the involvement of IFT43 in retinal degeneration.